The impact of the COVID-19 pandemic on the resources and activities of basic occupational health services in Poland - Andrzej Marcinkiewicz (Nofer Institute of Occupational Medicine, 2022)
Background In 2020, the first year of the COVID-19 pandemic, there were a number of factors affecting employees, employers, and consequently, both directly and indirectly, the occupational health service (OHS). The purpose of this publication is to analyze the activity of physicians and OHS units in this period in Poland. Material and Methods The analysis of the number of physicians, OHS units and their activities was performed on the basis of the MZ-35 and MZ-35A statistical forms, which represent obligatory medical reporting. Results There were 6349 occupational medicine physicians in Poland, who are entitled to conduct prophylactic examinations of employees and provide preventive health care, necessary due to working conditions (less by 248 [3.8%] compared to 2019). At the same time, the number of OHS basic units decreased to 5784 (by 3.2%). In 2020, occupational health physicians reported 4 314 520 prophylactic examinations of employees and job applicants, what is over 1 million 231 thousand (22.2%) less than in the year preceding the pandemic. In addition, they reported the performance of 255 887 prophylactic examinations related to the practical vocational training of pupils, students, participants in qualification vocational training and Ph.D. candidates (less by 157 220 [38.1%]). In 2020, they performed 1 933 355 preliminary examinations (23.9% less), 1 924 929 periodic examinations (25.1% less) and 456 236 follow-up examinations (5.1% more). In 2020, there was also a significant decrease in the number of visits to entire workplaces (from 6437 to 3625) and individual positions (from 46 197 to 26 389) carried out by OHS units. Also in 2020, an almost threefold increase (to 2183) in the number of suspected occupational diseases was reported by OHS physicians. In 2019, the duty to submit an annual report regarding prophylactic activities on the MZ-35A form has been obeyed by only 3607 (56.8%) obliged physicians. Conclusions The COVID-19 pandemic has significantly affected preventive activities carried out by occupational physicians. Med Pr. 2022;73(1):19-24